Dengue Virus Alters Sialic Acid Residues Configuration in Macrophages - Serrato-Salas, Javier; Cruz-Zazueta, Isabel; Montiel-Hernández, José Luis; González-Christen, Judith (bioRxiv, 2021)
Abstract The activation of the innate immune response requires sialic acid residues removal. Nevertheless, it is unknown the role for these changes during the Dengue virus infection. We determine if during Dengue virus infection, the sialic acid residues alter on the macrophages. The human monocytic cell line THP-1 was differentiated into macrophages and were infected with Dengue virus. The changes in sialic acid were evaluated by lectin blot in the cellular lysate. The activity of neuraminidase was defined by RT-PCR and fluorescence assays. Macrophages infection with DENV-2 reduces α-2,6 sialic acid residues at 24 h, and α-2,3 sialic acid residues lower at 48 h in some proteins. Transcriptional profile and enzymatic activities of Neu-1 showed a narrow decrease. Sialic acid residues oscillation in varied conformations and times suggest it a role of a selective mechanism to remove these residues. The lesser participation of Neu-1 in this process could be concomitant to other similar enzymes such as sialyl-transferases, or the phenomenon requires minimal activity to have a relevant biological function. Competing Interest Statement The authors have declared no competing interest.